Control of adhesive ligand density for modulation of nucleus pulposus cell phenotype. (August 2020) - Barcellona, Marcos N.; Speer, Julie E.; Fearing, Bailey V.; Jing, Liufang; Pathak, Amit; Gupta, Munish C.; Buchowski, Jacob M.; Kelly, Michael; Setton, Lori A.
Abstract: Cells of the nucleus pulposus have been observed to undergo a shift from their notochordal-like juvenile phenotype to a more fibroblast-like state with age and maturation. It has been demonstrated that culture of degenerative adult human nucleus pulposus cells upon soft (<1 kPa) full length laminin-containing hydrogel substrates promotes increased levels of a panel of markers associated with the juvenile nucleus pulposus cell phenotype. In the current work, we observed an ability to use soft polymeric substrates functionalized with short laminin-mimetic peptide sequences to recapitulate the behaviors elicited by soft, full-length laminin containing materials. Furthermore, our work suggests an ability to mimic features of soft systems through control of peptide density upon stiffer substrates. Specifically, results suggest that stiffer polymer-peptide hydrogel substrates can be used to promote the expression of a more juvenile-like phenotype for cells of the nucleus pulposus by reducing adhesive ligand presentation. Here we show how polymer stiffness combined with adhesive ligand presentation can be controlled to be supportive of nucleus pulposus cell phenotype and biosynthesis.